Adopting analytic hierarchy process to prioritise banks based on CRM effectiveness - the customers perspective. (2017) - Padmavathy, C.; Sivakumar, V.J.
Over the past few years, Indian private sector banks has placed stringent competition to public sector banks as the private sector banks pioneered in adopting newer technologies, broad product mix and, flexible offerings in products/services. To win the battle of competition, Indian banks today are focusing towards practicing customer relationship management effectiveness (CRME) to develop and maintain long-term customer relationships. This paper is an attempt to identify the most effective CRM bank with respect to varied CRM practices among the select banks. Sample of 42 retail bank customers were studied using analytic hierarchy process (AHP) for this purpose. The study findings set aside significant implications to each bank corresponding to each CRM practice (dimension).